Food habits of the Magellanic horned owl (Bubo virginianus magellanicus) at southernmost Patagonia, Argentina - Formoso, Anahí Elizabeth (2012)
The Magellanic Horned Owl (Bubo virginianus magellanicus) is the largest representative of the family Strigidae in southern South America and its distribution ranges from central Peru and western Bolivia southward through Chile and western Argentina as far as Tierra del Fuego Island (del Hoyo et al. 1999). This owl is currently classified as a subspecies of the Great Horned Owl ( B. virginianus ) although it is recognized by some authors as a full species because of its smaller size and differentiation in vocalizations, morphology, and DNA (del Hoyo et al. 1999). Its diet is composed mostly of small mammals, but birds and insects are also consumed (del Hoyo et al. 1999). Several diet studies have been conducted along its distributional range (e.g., Jaksic and Marti 1984, Ortiz et al. 2010); however, in Argentinean Patagonia, most studies were performed north of 48 u S (Dona ́zar et al. 1997, Teta et al. 2001, Trejo et al. 2005, Nabte et al. 2006). Most such stud- ies indicated that Magellanic Horned Owls are generalist predators feeding primarily on rodents, lagomorphs, and arthropods, in varying proportions according to habitat, season, and prey availability. Our goals in this study were (1) to characterize the diet of the Magellanic Horned Owl in austral Patagonia, and (2) to compare our findings with those previously reported for other regions.